2012
DOI: 10.1016/j.biortech.2011.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment optimization of Scenedesmus obliquus microalga for bioethanol production

Abstract: The present work deals with the optimization of cellular disruption and sugar extraction from the microalgae Scenedesmus obliquus (Sc) for bioethanol production. Among the physical and physicochemical methods tested, the best results were obtained with acid hydrolysis by H(2)SO(4) (2N), at 120 °C for 30 min and using dried biomass. The sugar extraction efficiency level reached was 95.6% when compared to the harsh quantitative acid hydrolysis. The influence of other parameters such as biomass loading and number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
91
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(118 citation statements)
references
References 30 publications
8
91
1
7
Order By: Relevance
“…In acid and alkaline methods, H 2 SO 4 is the most applied acid whereas NaOH is the most studied base. Treatments have been shown to be effective as pretreatment for fermentation and extraction of intercellular compounds such as lipids and pigments (Mendes-Pinto et al, 2001;Miranda et al, 2012;Nguyen et al, 2009). The reaction can be performed at ambient or elevated pressure, and temperatures above 100°C enhance reaction rates.…”
Section: (Bio)chemical Methods For Cell Wall Disruptionmentioning
confidence: 99%
“…In acid and alkaline methods, H 2 SO 4 is the most applied acid whereas NaOH is the most studied base. Treatments have been shown to be effective as pretreatment for fermentation and extraction of intercellular compounds such as lipids and pigments (Mendes-Pinto et al, 2001;Miranda et al, 2012;Nguyen et al, 2009). The reaction can be performed at ambient or elevated pressure, and temperatures above 100°C enhance reaction rates.…”
Section: (Bio)chemical Methods For Cell Wall Disruptionmentioning
confidence: 99%
“…The yield of ethanol from the fermentation of microalgal biomass has been found to be up to 38 % of the dry microalgal biomass (Harun et al 2010). An advantage of fermentation of microalgae may be that wet biomass could be used, but a recent study found that the sugar released from fermentation of dried biomass was 55 % higher than that from wet microalgal biomass (Miranda et al 2012). If the microalgal biomass needs to be dried prior to conversation to fermentable sugars for bioethanol production it is likely that bioethanol production will not be energy efficient or economic.…”
Section: Microalgal Bioethanolmentioning
confidence: 99%
“…A sugar extraction efficiency of 96 % has been achieved by acid hydrolysis of dried Scenedesmus biomass (Miranda et al 2012). …”
Section: Microalgal Bioethanolmentioning
confidence: 99%
“…Carbohydrates are mainly present in microalgae cell wall as cellulose and hemicellulose, and/or inside the cell as starch. Cell walls are mainly composed of biopolymers such as sporopollenin or algaenan, which 4 confer the cell a high rigidity and resistance to chemical attack (González-Hernández et al., 2012) and are characteristic of microalgae strains like Scenedesmus (Miranda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrates are mainly present in microalgae cell wall as cellulose and hemicellulose, and/or inside the cell as starch. Cell walls are mainly composed of biopolymers such as sporopollenin or algaenan, which 4 confer the cell a high rigidity and resistance to chemical attack (González-Hernández et al., 2012) and are characteristic of microalgae strains like Scenedesmus (Miranda et al, 2012).In order to make available the valuable compounds present inside microalgae cells, pretreatments are often needed in order to disrupt cell walls. Microalgae pretreatment allows for an efficient release of the carbohydrate content, enhancing saccharification and sugars bioavailability to maximize biofuels production (Hernández et al, 2015).…”
mentioning
confidence: 99%